Dynamics of development: an international perspective - Sharma, Sudesh Kumar (ed.) (Delhi, 1978)
The present volumes present, along a broad spectrum of interests and at different levels of analysis, some of the issues that the earlier genre of development theory brought up. It is useful to go over these writings for providing a generational overview to the present search for alternative paradigms and perspectives. They provide us with a useful benchmark against which we can try and understand the changing epistemology of social sciences.
Keywords: Economic development